2017
DOI: 10.1161/circep.117.005233
|View full text |Cite
|
Sign up to set email alerts
|

Progression From Esophageal Thermal Asymptomatic Lesion to Perforation Complicating Atrial Fibrillation Ablation

Abstract: Postablation endoscopy seems to identify patients at high risk of esophageal perforating complications only occurring in patients with category 2 EDEL. One out of 10 postablation esophageal ulcers progressed to perforation, and no patient without esophageal thermal ulcers showed the occurrence of perforating esophageal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 21 publications
1
116
0
8
Order By: Relevance
“…EDEL have been identified in between 0% and up to 40% of patients after AF ablation depending on ablation energy, type of ablation catheter, use of catheter‐tip irrigation, use of temperature probes, and depending on the indication and timing of postprocedural endoscopy . Endoscopy is considered the gold standard for detecting thermal esophageal damage and category 2 EDEL are the endoscopic findings in patients with increased risk of perforating esophageal injury like atrioesophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…EDEL have been identified in between 0% and up to 40% of patients after AF ablation depending on ablation energy, type of ablation catheter, use of catheter‐tip irrigation, use of temperature probes, and depending on the indication and timing of postprocedural endoscopy . Endoscopy is considered the gold standard for detecting thermal esophageal damage and category 2 EDEL are the endoscopic findings in patients with increased risk of perforating esophageal injury like atrioesophageal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy is considered the gold standard for detecting thermal esophageal damage and category 2 EDEL are the endoscopic findings in patients with increased risk of perforating esophageal injury like atrioesophageal fistula. A recently published study found an incidence of atrioesopahgeal fistula and esophageal perforation of 0.6% in patients undergoing rigid postablation surveillance . Of note, esophageal thermal injury can be identified using endoscopy already during the ablation procedure and most EDEL heal off within 7 days after the initial thermal injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations